MANAGEMENT OF AGROECOSYSTEMS AND FUNCTIONAL DIVERSITY OF SOIL-ASSOCIATED ARTHROPODS IN THE EASTERN AMAZON - Silva, Neilson Rocha; Guimarães, Eguinaldo dos Santos; Ferreira, Luziel Oliveira; Rodrigues, Diego Macedo (Geoambiente On-line, 2021)
In the Eastern Amazon, the change in vegetation cover by converting forest areas to pastures affects the diversity of arthropods, and non-conservationist management in these areas can reduce functional diversity, compromising the sustainability of the agroecosystem. Accordingly, the objective of this work was to analyze the composition of the functional groups of the arthropod community associated with the soil under different management regimes in agroecosystems in the Eastern Amazon. For this, the study was carried out in three agroecosystems, namely bean cultivation, cassava cultivation and pasture, and in an area of secondary forest used as a reference. Arthropods were captured by means of fall traps installed in the center of agroecosystems. The captured arthropods were identified at the order and family level and later grouped according to their function. A total of 19,850 individuals were collected and classified into six different functional groups: herbivores, social insects, omnivores, predators, saprophages and xylophages. The arthropods in bean and cassava cultivation agroecosystems were more abundant and diversified in most functional groups. The results revealed that agroecosystems with crop rotation and intercropping, with the incorporation of plant residues and associated with spontaneous plants favored the diversity of functional groups.